Pemodelan Genangan Banjir Sungai Opak, Kabupaten Bantul, Provinsi Daerah Istimewa Yogyakarta Menggunakan Software HEC-RAS V.5.0.7 - Asih, Andrea Sumarah; Anggi Hermawan (ReTII, 2023)
Every year along the riverbanks of the Opak River area, Bantul Regency experiences flooding. The purpose of this research is to determine the annual design flood discharge in the Opak River and then model the results of flood inundation so that it can determine the area of the village and the area of land cover affected by flooding in the 25-year return period (Q25) in the Kretek-Hilir Dam sub-basin with a flow length of Â± 4.45 km. This research uses secondary data, namely: topographic map, geometry, and hydrology data. The analysis started with hydrological analysis, namely analyzing the rainfall of Kali Opak watershed from 2010-2020 using Thiessen Polygon method and using ArcGIS application for depiction and calculation of Thiessen Polygon area and map. Unit hydrograph analysis using the HSS Nakayasu method to produce a planned flood discharge for each sub-watershed with 25 years, after obtaining the planned flood discharge for each sub-watershed then flood inundation modeling is carried out using HEC-RAS and assisted by ArcGIS software.The results of the data analysis of the 25-year return period total discharge, which is obtained from adding the discharge from all sub-watersheds of the opak river, is the result of a discharge of 1733.65 m3/s with a total flood inundation area in the village around the affected river of 1575247.32 m2 or 157.26 ha.